Of parties, rites and battles: Some folk behaviors of the Andean society of the K'anas and Ch'umpiwillcas - Zecenarro Villalobos, Bernardino (1992)
The present work is framed within the context of the so-called "Andean anthropology", since it aims to clarify a type of socio-cultural behavior that characterizes the Andean society of the k'anas and ch'umpiwillkas. Traditional inhabitants of the "upper provinces" of the department of Cusco, that is, Kanas, Espinar and Chumbivilcas, the current k'anas and ch'umpiwillkas are proud of their Qolla lineage, which gave them a certain fame after the Tupac Amaru rebellion. , as this is a native of the province of Kanas. The folk behaviors that are presented somehow reflect this situation, although each one of them is the product of a long historical-social process.